2014
DOI: 10.1007/s11926-014-0421-z
|View full text |Cite
|
Sign up to set email alerts
|

Spondyloarthritis in Sub-Saharan Africa

Abstract: Spondyloarthritis (SpA) is generally uncommon in sub-Saharan Africa, in part because of the rarity of HLA-B27 in this region. However, the relationship between HLA-B27 and SpA, particularly ankylosing spondylitis (AS), is complex. Despite the HLA-B 27:05 risk allele occurring in some West African populations, associated AS is not seen. In fact, most patients with AS are HLA-B27-negative, although there is emerging evidence that another class I HLA molecule, HLA-B 14:03, is associated with AS in black Africans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 32 publications
5
27
0
1
Order By: Relevance
“…This was first noted in a cross-sectional survey of 1352 South African blacks in a study in 1975 5 . In more recent reviews of the subject, similar findings were found from other parts of Africa 6,7 .…”
Section: Spondyloarthritis In African Blackssupporting
confidence: 77%
“…This was first noted in a cross-sectional survey of 1352 South African blacks in a study in 1975 5 . In more recent reviews of the subject, similar findings were found from other parts of Africa 6,7 .…”
Section: Spondyloarthritis In African Blackssupporting
confidence: 77%
“…The clinical presentation of the disease is similar to that of the Caucasian subject [5]; however, extra-articular manifestations seem rare [10]. There was no statistically significant difference by gender.…”
Section: Z T W Joelle Et Alsupporting
confidence: 50%
“…The rarity of AS in sub-Saharan Africa seems to be related to the scarcity of HLA B27 antigen. HLA-B 14:03 is evoked as possibly associated with the black African SA [5]. Indeed, this allele was found in 4 among the 8 SA patients seen in Togo and among any control and in 2 of the 3 SA patients seen in Zambia [2] [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HLA B 27 studies were however not done in our patient. Studies in African patients document absence of HLA B27, and possible HLA B14 association to reactive arthritis [17]. …”
Section: Discussionmentioning
confidence: 99%